Pemanfaatan Lingkungan Sekitar Peserta Didik sebagai Sumber Pembelajaran IPA untuk Meningkatkan Motivasi Belajar - Ghina Zakiah; Melva Zainil (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
This article discusses the importance of utilizing the surrounding environment as a source of learning Natural Sciences (IPA) in Elementary Schools (SD). IPA learning, which is often dominated by textbooks and lectures, can cause students to lose motivation and have difficulty understanding abstract concepts. By involving the surrounding environment, such as the school and home environment, students gain a more concrete, interesting, and meaningful learning experience. This research uses the Systematic Literature Review method to analyze various relevant library sources. The results of the analysis show that the utilization of the surrounding environment can increase student motivation, develop science process skills, and foster a positive attitude towards the environment. Although there are challenges in its implementation, such as ensuring the availability of a safe and appropriate environment, these challenges can be overcome with careful planning and creativity from teachers.